(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
The term "diaspora" refers to the dispersion of people from their original homeland to various parts of the world. Historically associated with involuntary dispersion due to conflict, persecution, or economic hardship, contemporary usage includes voluntary migrations driven by economic opportunities, education, or quality of life improvements. Nepali migration, which began in the late 19th and early 20th centuries primarily to India, has significantly expanded in the latter half of the 20th century and early 21st century to countries such as the United States, the United Kingdom, Australia, Canada, and Gulf countries. This migration has fostered vibrant Nepali diasporic communities worldwide, characterized by a strong retention of cultural heritage and traditions. The objective of this research is to conduct a comprehensive analysis of Nepali diasporic writings, exploring the themes, cultural contexts, key authors, and the broader significance of these narratives. The methodology involves qualitative analysis of published literary works, academic articles, and interviews with Nepali writers. The findings reveal that Nepali diasporic literature extensively explores themes of migration, cultural adaptation, nostalgia, and generational conflicts. Notable authors like Samrat Upadhyay, Manjushree Thapa, and Sushma Joshi highlight the complexities of maintaining cultural continuity while adapting to new environments. The conclusion emphasizes that Nepali diasporic writings not only preserve cultural identity but also enrich the global literary landscape with diverse narratives, fostering cross-cultural understanding and highlighting the interconnectedness of diverse cultural experiences. Навигацийн таних тэмдэг: Балбын диаспорын уран зохиол дахь соёлын залгамж чанар Хураангуй: "Диаспора" гэсэн нэр томъёо нь эх орноосоо дэлхийн янз бүрийн хэсэгт тархан сууршсан хүмүүсийг хэлдэг. Мөргөлдөөн, хавчлага, эдийн засгийн хүндрэлийн улмаас өөрийн эрхгүй таран сууршсан түүхэн шалтгаантай холбоотой байдаг бөгөөд энэ ойлголтын орчин үеийн хэрэглээ нь эдийн засгийн боломж, боловсрол, амьдралын чанарыг сайжруулах зэргээс үүдэлтэй сайн дурын шилжилт хөдөлгөөнийг багтаадаг. 19-р зууны сүүлч, 20-р зууны эхэн үеэс Энэтхэгт эхэлсэн Балбын нүүдэл 20-р зууны сүүлийн хагас, 21-р зууны эхэн үед АНУ, Их Британи, Австрали, Канад, Персийн булан зэрэг улс орнуудад ихээхэн өргөжин тэлсэн. Энэхүү шилжилт хөдөлгөөн нь дэлхийн хэмжээнд соёлын өв, уламжлалаа хүчтэй хадгалан үлддэг Балбын диаспоруудын эрч хүчтэй бүлгүүдийг бий болгосон. Тус судалгааны зорилго нь Балбын диаспорын бичвэрүүдэд иж бүрэн дүн шинжилгээ хийж, сэдэв, соёлын нөхцөл байдал, гол зохиогчид болон эдгээр өгүүлэмжийн илүү өргөн ач холбогдлыг судлах явдал юм. Аргачлалын хувьд хэвлэгдсэн уран зохиолын бүтээл, эрдэм шинжилгээний өгүүлэл, Балбын зохиолчидтой хийсэн ярилцлага зэрэгт чанарын дүн шинжилгээ хийлээ. Судалгааны үр дүнд Балбын диаспорын уран зохиолд цагаачлал, соёлын дасан зохицох, дурсамж, үе үеийн зөрчилдөөн зэрэг сэдвүүдийг өргөнөөр тусгадаг болохыг харуулж байна. Samrat Upadhyay, Manjushree Thapa, Sushma Joshi зэрэг алдартай зохиолчид шинэ орчинд дасан зохицохын зэрэгцээ соёлын залгамж чанарыг хадгалах нарийн төвөгтэй байдалд байдгийг онцлон тэмдэглэв. Балбын диаспорын зохиолууд нь соёлын өвөрмөц байдлыг хадгалаад зогсохгүй дэлхийн утга зохиолын ландшафтыг олон янзын өгүүлэмжээр баяжуулж, соёл хоорондын харилцан ойлголцлыг бий болгож, олон янзын соёлын туршлагын харилцан уялдааг голчлон тусгаж буйг онцгойлон дүгнэлээ. Түлхүүр үг: Диаспора, өвөрмөц байдал, соёлын дасан зохицох, дурсах, нүүлгэн шилжүүлэх